Biochar and compost from cotton residues inconsistently affect water use efficiency, nodulation, and growth of legumes under arid conditions. (1st April 2022) - Haddad, Samir A.; Mowrer, Jake; Thapa, Binita
Abstract: There is an urgent global need to expand crop cultivation into arid and semiarid lands to guarantee food security. Thus, limited irrigation strategies and soil amendments are promising strategies for conserving water in arid and semi-arid crop production. Soil amendments, such as compost and biochar can improve soil water relationships, nitrogen (N) fixation, soil fertility, and crop productivity. A study was designed to evaluate the effect of biochar and compost applications on soil water relationships, nutrient uptake, plant growth, and N-fixation. A greenhouse pot experiment was conducted in two soils using a complete factorial design. The main effect, i.e., water content of each soil, was maintained at either 40% or 60% water filled porosity. The sub-effect, organic amendment type, was applied as biochar or compost. The sub-sub effect was rate of application (0, 5, and 10 Mg ha −1 ). Plant height and root length were significantly affected by the rate of amendment applied, whereas shoot and root mass differences were explained by irrigation strategy. Whole plant N uptake was moderately affected by water content only (p = 0.0818). Phosphorus and Potassium uptake were highly affected by amendment type and rate. Biochar moderately improved plant available water (0.061 %Vol Mg −1 ha −1 ) over the range of 0–20 Mg ha −1 in the sandier soil. Compost did not improve plant available water in either soil. Nodulation was affected by soil type only. The benefits of biochar or compost for plant were inconsistent and depended upon irrigation strategies, soil type, application rate, and plant species. Graphical abstract: Image 1 Highlights: Plant parameters were significantly affected by the rate of biochar or compost. Amended sandy soil showed moderate improvement in plant available water. Water content and the amendment rate had a significant effect on shoot/root mass. Benefits towards plant growth following biochar or compost rates were inconsistent.